Adolescents: Contraceptive Knowledge and Use, a Brazilian Study - Divanise S. Correia; Ana C. P. Pontes; Jairo C. Cavalcante; E. Sócrates T. Egito; Eulália M.C. Maia (The Scientific World Journal)
The purpose of this study was to identify the knowledge and use of contraceptive methods by female adolescent students. The study was cross-sectional and quantitative, using a semi-structured questionnaire that was administered to 12- to 19-year-old female students in Maceió, Brazil. A representative and randomized sample was calculated, taking into account the number of hospital admissions for curettage. This study was approved by the Human Research Ethics Committee, and Epi InfoTM software was used for data and result evaluation using the mean and chi-square statistical test. Our results show that the majority of students know of some contraceptive methods (95.5%), with the barrier/hormonal methods being the most mentioned (72.4%). Abortion and aborting drugs were inaccurately described as contraceptives, and 37.9% of the sexually active girls did not make use of any method. The barrier methods were the most used (35.85%). A significant association was found in the total sample (2,592) between pregnancy and the use of any contraceptive method. This association was not found, however, in the group having an active sexual life (559). The study points to a knowledge of contraceptive methods, especially by teenagers who have already been pregnant, but contraceptives were not adequately used. The low use of chemical methods of contraception brings the risk of pregnancy. Since abortion and aborting drugs were incorrectly cited as contraceptive methods, this implies a nonpreventive attitude towards pregnancy.